Sagot :
[tex]\red{\bold{\large{SOLUTION}}}[/tex]
[tex] \frac{8}{9} - \frac{1}{3} = \: ?[/tex]
[tex] = \frac{(8 \times 3) - (1 \times 9)}{9 \times 3} [/tex]
[tex] = \frac{24 \: - \: 9}{27} [/tex]
[tex] = \frac{15}{27} [/tex]
Reduce by dividing both the numerator and denominator by the Greatest Common Factor GCF(15,27) = 3
[tex] = \frac{15 \: \div \: 3 }{27 \: \div \: 3} = \frac{5}{9} [/tex]
[tex] \frac{8}{9} - \frac{1}{3} = \frac{5}{9} [/tex]
[tex] \red{\bold{\large{ANSWER}}}[/tex]
[tex] \frac{8}{9} - \frac{1}{3} = \frac{5}{9} [/tex]
[tex]\blue{\boxed{\bold{C. \: \frac{5}{9} }}}[/tex]
#CarryOnLearning
![View image Elizacornelio60](https://ph-static.z-dn.net/files/d5c/a3058af9227dbcad5d8e1b09da114abb.jpg)
![View image Elizacornelio60](https://ph-static.z-dn.net/files/d90/4039a9a29e4b00a127c46103b06ee158.jpg)